Yhhu981, a novel compound, stimulates fatty acid oxidation via the activation of AMPK and ameliorates lipid metabolism disorder in ob/ob mice - Zeng, Hong-liang (Acta Pharmacol Sin, 2015)
AIM: Defects in fatty acid metabolism contribute to the pathogenesis of insulin resistance and obesity. In this study, we investigated the effects of a novel compound yhhu981 on fatty acid metabolism in vitro and in vivo. METHODS: The capacity to stimulate fatty acid oxidation was assessed in C2C12 myotubes. The fatty acid synthesis was studied in HepG2 cells using isotope tracing. The phosphorylation of AMPK and acetyl-CoA carboxylase (ACC) was examined with Western blot analysis. For in vivo experiments, ob/ob mice were orally treated with yhhu981 acutely (300 mg/kg) or chronically (150 or 300 mg·kg(−1)·d(−1) for 22 d). On the last day of treatment, serum and tissue samples were collected for analysis. RESULTS: Yhhu981 (12.5–25 μmol/L) significantly increased fatty acid oxidation and the expression of related genes (Sirt1, Pgc1α and Mcad) in C2C12 myotubes, and inhibited fatty acid synthesis in HepG2 cells. Furthermore, yhhu981 dose-dependently increased the phosphorylation of AMPK and ACC in both C2C12 myotubes and HepG2 cells. Compound C, an AMPK inhibitor, blocked fatty acid oxidation in yhhu981-treated C2C12 myotubes and fatty acid synthesis decrease in yhhu981-treated HepG2 cells. Acute administration of yhhu981 decreased the respiratory exchange ratio in ob/ob mice, whereas chronic treatment with yhhu981 ameliorated the lipid abnormalities and ectopic lipid deposition in skeletal muscle and liver of ob/ob mice. CONCLUSION: Yhhu981 is a potent compound that stimulates fatty acid oxidation, and exerts pleiotropic effects on lipid metabolism by activating AMPK.